The Perspectives of the renewable power generation development in Russia; 7 international conference on technical and phisical problems of power engineering, ICTPE-2011 - Ushakov V. Ya. Vasily Yakovlevich (2011, 2011)
В фонде НТБ ТПУ отсутствует